Pricing behavior in Philippine corn markets: implications for market efficiency - Mendoza, Meyra Sebello; Rosegrant, Mark W. (International Food Policy Research Institute, 1995)
The future for Philippine corn looks bright. Increases in demand for feed for livestock and poultry, activated by income-led growth in demand for meat, are providing the major push for corn growth. But whether the potential for development can be reached hinges on the efficiency of the existing marketing and pricing system. In Pricing Behavior in Philippine Corn Markets: Implications for Market Efficiency, Research Report 101, Meyra Sebello Mendoza and Mark W. Rosegrant explore this issue by determining the speed with which price signals are communicated between markets and quantifying the impact of new information on the pricing process. In determining whether market information is transmitted completely and on time to Filipino corn farmers, they identify possible constraints faced by farmers.